Respuesta :

Answer:

Answer:

X

The given statement is true.

Step-by-step explanation:

An inverse function can be defined as  a function that "reverses" another function: if the function f applied to an input x gives a result of y, then applying its inverse function g to y gives the result x, and vice versa, i.e., f(x) = y if and only if g(y) = x.

Examples are x+2 and x-2

WE get f(x) = x+2

Apply g(x) = g(f(x))=g(x+2)

=x+2-2=x

Thus by applying composiiton g f or fg in any order we get the answer as x

THis is the property of any inverse function

Step-by-step explanation:

Answer:

X

Step-by-step explanation:

It was corrected on E2020.